Penerapan Pelayanan Asuhan Kebidanan Bayi Balita di Praktik Bidan Mandiri (PMB) pada Masa Pandemi COVID-19 - Maya Indriati; Rosita Rosita (Sehat MasadaJurnal, 2021)
COVID-19 has been declared a world pandemic by WHO in 2020. The government has the responsibility to ensure every citizen, including children, to obtain basic health services. At the Posyandu level, 86% of health facilities reported cessation of development and growth monitoring, 55% reported cessation of immunization services and 46% reported cessation of vitamin delivery services, and 46% cessation of antenatal care services. This research used descriptive qualitative research method, by involving 2 midwives in independent midwife (PBM) and 2 parents who have babies and toddlers who got services at the independent midwife (PBM). During this pandemic, independent midwife (PBM) is still providing services as usual and there are no health protocols that must be carried out by service recipients during their visit. The number of visits showed a decrease, due to restrictions on visits for babies who did not have serious problems and needed action. There are factors that become obstacles in implementing services for infants and toddlers during this pandemic such as parental knowledge is lacking, there has been no socialization about services during the pandemic, and parents are afraid to come to the service. Supporting factors for the implementation of services obtained several important themes, including the support of health workers, and the importance of examining babies and toddlers independently at home. It is hoped that parents who have babies and toddlers will continue to monitor the health of their babies and toddlers even at home by looking for various information either from the media or being able to consult with health workers.